Lipid Polymorphism of the Subchloroplast-Granum and Stroma Thylakoid Membrane-Particles. II. Structure and Functions - Dlouhý, Ondřej; Karlický, Václav; Arshad, Rameez; Zsiros, Ottó; Domonkos, Ildikó; Kurasová, Irena; Wacha, András F; Morosinotto, Tomas; Bóta, Attila; Kouřil, Roman; Špunda, Vladimír; Garab, Győző (Cells, 2021)
In Part I, by using 31P-NMR spectroscopy, we have shown that isolated granum and stroma thylakoid membranes (TMs), in addition to the bilayer, display two isotropic phases and an inverted hexagonal (HII) phase; saturation transfer experiments and selective effects of lipase and thermal treatments have shown that these phases arise from distinct, yet interconnectable structural entities. To obtain information on the functional roles and origin of the different lipid phases, here we performed spectroscopic measurements and inspected the ultrastructure of these TM fragments. Circular dichroism, 77 K fluorescence emission spectroscopy, and variable chlorophyll-a fluorescence measurements revealed only minor lipase- or thermally induced changes in the photosynthetic machinery. Electrochromic absorbance transients showed that the TM fragments were re-sealed, and the vesicles largely retained their impermeabilities after lipase treatments-in line with the low susceptibility of the bilayer against the same treatment, as reflected by our 31P-NMR spectroscopy. Signatures of HII-phase could not be discerned with small-angle X-ray scattering-but traces of HII structures, without long-range order, were found by freeze-fracture electron microscopy (FF-EM) and cryo-electron tomography (CET). EM and CET images also revealed the presence of small vesicles and fusion of membrane particles, which might account for one of the isotropic phases. Interaction of VDE (violaxanthin de-epoxidase, detected by Western blot technique in both membrane fragments) with TM lipids might account for the other isotropic phase. In general, non-bilayer lipids are proposed to play role in the self-assembly of the highly organized yet dynamic TM network in chloroplasts.
Keywords: Thylakoids; lipidy; magnetická rezonanční spektroskopie; Photosynthesis; Magnetic Resonance Spectroscopy; Circular Dichroism; tylakoidy; cirkulární dichroismus; Lipids; fotosyntéza; Microscopy, Electron; elektronová mikroskopie